Kill Bill or Tax: An Analysis of Alternative CO₂ Price Floor Options for EU Member States - Christoph Böhringer; Carolyn Fischer (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Several EU member states are exploring options for setting minimum domestic carbon prices within the EU Emission Trading System (ETS). First, a "TAX" policy would introduce a carbon tax equal to the difference between the prevailing ETS price and the targeted minimum price. Second, a national auction reserve price would "KILL" allowances by invalidating them until the ETS price equalled the national minimum price. Third, a government could require domestic overcompliance and "BILL" covered entities for extra allowances per ton of emissions, thereby increasing demand for allowances and pulling up the ETS price. We explore the implications of these policy options on national and ETS-wide carbon prices, revenues from emissions allowances, emissions, and economic welfare. We find that a national government's preferred unilateral policy will depend on the extent to which it values the fiscal benefits of revenues, which favor TAX or to a lesser degree BILL, versus climate benefits, which favor KILL and also BILL, particularly for jurisdictions with more emissions to leverage for overcompliance. Our analysis can be generalized to other multilateral cap-and-trade systems where participants pursue more stringent internal emission pricing through unilateral policies.
Keywords: H23; Q58; D62; 330; CO2 price floor; emissions trading; carbon tax